Kualitas Air dan Struktur Komunitas Plankton di Perairan Pantai Lovina Kabupaten Buleleng Provinsi Bali - Ginting, Irene Yolanda Br; Restu, I Wayan; Pebriani, Dewa Ayu Angga (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019), 2018)
Lovina Beach is one of the beaches visited by many foreign and domestic tourists. Lovina Beach has a tourism spot and a vast area of marine biota cultivation. Life of biota in the waters of Lovina Beach is affected by conditions of beach waters. The research purpose was to know the correlation between waters quality and plankton in Lovina Beach by using observation method. The research was done on February until March 2017. Species of fitoplankton species from all three stations was dominated by Lyngbya sp. with abundance of 78 ind/l. The average value of the phytoplankton diversity index found was 1.7706. The average value of phytoplankton uniformity index is 0.9882 while the value of phytoplankton dominance index is 0.1737. The average value of the zooplankton diversity index found is 1.7311. The average value of the zooplankton uniformity index is 0.8896 while the zooplankton dominance index value is 0.2125. The result of the measurement of water quality is temperature parameter in Lovina Beach ranged from 27.6 - 28.9 0C, brightness ranged between 4.7 - 6 m, salinity of 25.3 - 27 ppt, DO (Dissolved Oxygen) ranged between 4 - 4 , 7 Mg / L, the pH ranged from 8.5 to 8.6, the nitrate ranged from 0.0081-00087 Mg/L and the phosphate ranged from 0.016 to 0.027 Mg / L. So, it can be concluded that the waters of Lovina Beach has the highest abundance of plankton that is the type of zooplankton, the level of plankton community structure in Lovina Beach waters is moderate.ppt, DO (Dissolved Oxygen) 4 – 4,3 Mg/l, pH 8,5 – 8,6, nitrate 0,0081 – 0,0087 Mg/l and phosphate 0,016 – 0,027 Mg/L. The structure of plankton community in Lovina coastal according of phytoplankton abundance categorized in oligotropic, while according of zooplankton abundance categorized in moderate (mesotropic).